Safety of alitretinoin for severe refractory chronic hand eczema: Clinical studies and postmarketing surveillance. (2nd January 2016) - Morris, Marc; Schifano, Lorrie; Fong, Regan; Graff, Ole
Abstract: Background : Alitretinoin is approved for the treatment of adults with severe chronic hand eczema (CHE) refractory to potent topical steroids. In the 6 years since launch, approximately 250 000 patients have been treated with alitretinoin. Objective : To compare the postmarketing safety surveillance experience of alitretinoin with data from clinical trials and key safety issues with other retinoids. Methods : An integrated safety analysis of the pivotal studies of alitretinoin and postmarketing adverse event (AE) reports received since approval for alitretinoin were analyzed. Results : In the pivotal trials, headache, erythema, nausea, increased blood triglycerides and increased blood creatinine phosphokinase were the most frequently reported AEs. Headache, hyperlipidemia and nausea were also frequently reported postmarketing AEs, but depression was relatively more frequently reported than in the pivotal trials. Inflammatory bowel disease and benign intracranial hypertension were rare, and very few cases have been reported in postmarketing surveillance. There have been no reports of teratogenicity in humans consequent to fetal exposure. Conclusions : Safety data collected in pivotal trials and postmarketing surveillance suggest that alitretinoin is well tolerated by patients with CHE with a relatively low incidence of serious reactions. The adverse reaction profile is congruent with reported effects of other marketed oral retinoids.